Knowledge, Attitudes and Actions of Farmers in Integrated Pest Management (IPM) in Purwoasri Village, Singosari District, Malang Regency - Yulianto, Teguh; Rahardjo, Bambang Tri (Journal of Tropical Plant Protection, 2025)
The Integrated Pest Management (IPM) program was implemented by the government from 1989-1998 through Integrated Pest Management Farmer Field School (IPM-FFS) activities. However, not all regions received this socialization. The uneven socialization activities regarding IPM have resulted in not all farmers having good knowledge about IPM and not all attitudes and actions taken by farmers are in accordance with IPM. Therefore it is necessary to study the evaluation of the level of success of the IPM program that has been implemented. The research was conducted in Purwoasri Village and Langlang Village by interviewing 20 farmers from each village with a questionnaire containing farmer characteristics, farming characteristics, knowledge, attitudes and actions of farmers in IPM. The data obtained was analyzed descriptively by simplifying the data to make it easier to interpret. The results of the research show that the IPM program in Purwoasri Village has been quite successful because IPM farmers are better than nonIPM farmers in terms of farming characteristics, knowledge, attitudes and actions in IPM.